Luis de Molina on “ middle knowledge” and human free will - HUANG, Jia (Journal of Research for Christianity in China (JRCC), 2025)
Molinaldism stands as a quintessential representation of Jesuit theology during the Catholic Reformation, its most distinctive feature being the reconciliation of divine grace with human free will. This paper examines Molinari's concept of human freedom, describing four states of humanity, and explores how his doctrine of “middle knowledge” safeguards human free will without conflicting with God's omniscience. This paper emphasizes a comprehensive presentation of Molinism's innovations within the historical context of the Catholic Reformation and the developmental trajectory of related theological concepts, aiming to foster a more thorough understanding of theological debates during this period.